Evidence for non-colligative function of small cryoprotectants in a freeze-tolerant insect - Toxopeus, Jantina; Koštál, Vladimír; Sinclair, Brent J (Proceedings - Royal Society. Biological sciences, 2019)
Freeze tolerance, the ability to survive internal ice formation, facilitates survival of some insects in cold habitats. Low-molecular-weight cryoprotectants such as sugars, polyols and amino acids are hypothesized to facilitate freeze tolerance, but their in vivo function is poorly understood. Here, we use a combination of metabolomics and manipulative experiments in vivo and ex vivo to examine the function of multiple cryoprotectants in the spring field cricket Gryllus veletis. Cold-acclimated G. veletis are freeze-tolerant and accumulate myo-inositol, proline and trehalose in their haemolymph and fat body. Injecting freeze-tolerant crickets with proline and trehalose increases survival of freezing to lower temperatures or for longer times. Similarly, exogenous myo-inositol and trehalose increase ex vivo freezing survival of fat body cells from freeze-tolerant crickets. No cryoprotectant (alone or in combination) is sufficient to confer freeze tolerance on non-acclimated, freeze-intolerant G. veletis. Given that each cryoprotectant differentially impacts survival in the frozen state, we conclude that small cryoprotectants are not interchangeable and likely function non-colligatively in insect freeze tolerance. Our study is the first to experimentally demonstrate the importance of non-colligative cryoprotectant function for insect freeze tolerance both in vivo and ex vivo, with implications for choosing new molecules for cryopreservation.
Keywords: nymfa; metabolomika; Freezing; Metabolomics; aklimatizace; Cold Temperature; Proline; mužské pohlaví; dlouhověkost; Cryoprotective Agents; nízká teplota; Acclimatization; Longevity; Gryllidae; Hemolymph; hemolymfa; Trehalose; trehalosa; Fat Body; zvířata; Nymph; prolin; zmrazování; kryoprotektivní látky; tukové těleso; Male; Animals